2007
DOI: 10.3758/bf03194035
|View full text |Cite
|
Sign up to set email alerts
|

Learning is impaired by activated intentions

Abstract: Two experiments examined the task interference that sometimes accrues from having an intention. In standard prospective memory tasks, latency is often slower to an ongoing task performed concurrently with having an intention than it is when no intention is given. If the locus of this slowing resulted from different attentional allocation policies in the two cases, we predicted that the process of learning a word list would be impaired if participants had an intention rather than if they did not. Four different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
(30 reference statements)
1
17
1
Order By: Relevance
“…The present data may appear at odds with the finding of Cook, Marsh, Clark-Foos, and Meeks (2007) that PM tasks imposed on participants when lists of words were studied decreased the subsequent recall of those words. Cook et al concluded that PM task requirements during the study phase drew attention away from the creation of interitem associations that support free recall.…”
Section: Discussioncontrasting
confidence: 56%
“…The present data may appear at odds with the finding of Cook, Marsh, Clark-Foos, and Meeks (2007) that PM tasks imposed on participants when lists of words were studied decreased the subsequent recall of those words. Cook et al concluded that PM task requirements during the study phase drew attention away from the creation of interitem associations that support free recall.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, when participants perform a lexical decision task and possess an intention to respond to a nonfocal cue, they perform the task more slowly than a control group without an intention (Marsh et al, 2003). Evidence for such task interference from having an intention to respond to cues has also been found in a multitude of other experimental paradigms (Cook, Marsh, Clark-Foos, & Meeks, 2007;Smith, 2003). Although costs to ongoing-task performance have been found in many studies, convincingly demonstrated that under certain conditions, there are not always commensurate increases in ongoing-task latencies when participants hold focal event-based intentions.…”
mentioning
confidence: 84%
“…However, these costs are attributable to a period of reorientation that occurs irrespective of the state of one's goals (for a review, see Monsell, 2003). Another interference effect can occur when two goals are pursued simultaneously (Cohen, Jaudas, & Gollwitzer, 2008;Cook, Marsh, Clark-Foos, & Meeks, 2007;Einstein et al, 2005;Hicks, Marsh, & Cook, 2005). Neither of these effects, however, speaks to the interference that may come from a previously unfulfilled intention.…”
mentioning
confidence: 93%